2020
DOI: 10.1126/scitranslmed.aaz8631
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic responses to Roseomonas mucosa in atopic dermatitis may involve lipid-mediated TNF-related epithelial repair

Abstract: Dysbiosis of the skin microbiota is increasingly implicated as a contributor to the pathogenesis of atopic dermatitis (AD). We previously reported first-in-human safety and clinical activity results from topical application of the commensal skin bacterium Roseomonas mucosa for the treatment of AD in 10 adults and 5 children older than 9 years of age. Here, we examined the potential mechanism of action of R. mucosa treatment and its impact on children with AD less than 7 years of age, the most common age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 80 publications
(104 reference statements)
1
91
0
2
Order By: Relevance
“…We previously demonstrated the importance of STAT3 in the scratch assay, an in vitro model of epithelial to mesenchymal transition (EMT; a central process of proliferation and migration of epithelial cells) mediated wound healing in patients with autosomal dominant hyper IgE syndrome due to STAT3 loss of function (STAT3LOF) [14]. We additionally demonstrated a role for STAT3 in the therapeutic response to the commensal flora Roseomonas mucosa in atopic dermatitis [15]. The influence of STAT3 on Warburg physiology as well as on cell proliferation and migration require concurrent activation of JAK2 [5,12,16].…”
Section: Introductionmentioning
confidence: 96%
“…We previously demonstrated the importance of STAT3 in the scratch assay, an in vitro model of epithelial to mesenchymal transition (EMT; a central process of proliferation and migration of epithelial cells) mediated wound healing in patients with autosomal dominant hyper IgE syndrome due to STAT3 loss of function (STAT3LOF) [14]. We additionally demonstrated a role for STAT3 in the therapeutic response to the commensal flora Roseomonas mucosa in atopic dermatitis [15]. The influence of STAT3 on Warburg physiology as well as on cell proliferation and migration require concurrent activation of JAK2 [5,12,16].…”
Section: Introductionmentioning
confidence: 96%
“…A recent publication from our group identified therapeutic benefit of topical microbiome transplantation of Roseomonas mucosa from healthy volunteers to the lesions of patients with AD (129). Subsequent research found that lipid mediators from R. mucosa stimulate EMT through potentiation of tumor necrosis factor receptor 2 and nicotinic acetylcholine activation; an additional role for flagella interactions with Toll-Like Receptor 5 was identified (113). This finding was consistent with our prior results in autosomal-dominant hyper IgE syndrome, a primary immune deficiency with an eczematous phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating the skin or gut microbiome appears as an appealing approach. Recent data conducted in atopic dermatitis skin, demonstrated that topical formulation containing specific strains of probiotics could improve skin lesions (62). Additional studies are urgently needed, especially those in vitiligo, but modulation of microbiome, using prebiotics, probiotics, postbiotics, or fecal microbiota transplantation, could be an alternative approach for secondary prevention in vitiligo.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%